Transformasi Metode Pembelajaran Fiqh Ibadah melalui Media Digital: Tantangan dan Peluang - Ali, Muhammad; Kurniawan, Dwi; Pratama, Mediyan (Tarbawiyah Jurnal Ilmiah Pendidikan, 2025)
Digital transformation in education has opened new opportunities for teaching Fiqh Ibadah in Islamic educational institutions. This study aims to explore the role of digital media in enhancing students' understanding of Fiqh Ibadah and to identify the challenges and opportunities encountered in its implementation. The research method employed in this study includes a literature review and case studies from several Islamic educational institutions that have adopted digital media in their teaching. The findings indicate that digital media, such as augmented reality (AR) and interactive Fiqh applications, can improve students' understanding of Ibadah practices such as wudu and salah. The use of this technology also enriches the learning experience by providing more realistic and interactive simulations of religious practices. However, the implementation of digital media in Fiqh Ibadah teaching faces major challenges, including infrastructure limitations, low digital literacy among teachers and students, and difficulties in translating Ibadah materials that require direct practice. Despite these challenges, there are significant opportunities to optimize the use of digital technology, particularly through digital literacy training and the development of learning applications. Therefore, collaboration between educational institutions, the government, and society is needed to overcome these challenges and improve the quality of digital media-based Fiqh Ibadah education.